2016
DOI: 10.1017/s0007114516004360
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-oestrogens and colorectal cancer risk: a systematic review and dose–response meta-analysis of observational studies

Abstract: Epidemiological studies suggest that soya consumption as a source of phyto-oestrogens and isoflavones may be associated with a reduced risk of colorectal cancer. However, findings have not yet been synthesised for all groups of phyto-oestrogens. A meta-analysis was conducted to quantify the association between phyto-oestrogens and colorectal cancer risk. Relevant observational studies published up to June 2016 were identified by searching MEDLINE, EMBASE and Cochrane Library databases. Study-specific relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 63 publications
(230 reference statements)
0
22
0
1
Order By: Relevance
“…Analyses by tumour subsite and UICC stage of the association between prediagnosis enterolactone concentrations as continuous (per doubling) and all-cause mortalitywomen and men diagnosed with colorectal cancer from the Diet, Cancer and Health cohort* (Numbers, hazard ratios (HR) and 95 % confidence intervals) selection bias similar to the so-called obesity paradox (39) . However, it may not be a major concern in the present study, because no strong association between enterolactone concentrations and colorectal cancer risk has been found in prospective studies (14) .…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Analyses by tumour subsite and UICC stage of the association between prediagnosis enterolactone concentrations as continuous (per doubling) and all-cause mortalitywomen and men diagnosed with colorectal cancer from the Diet, Cancer and Health cohort* (Numbers, hazard ratios (HR) and 95 % confidence intervals) selection bias similar to the so-called obesity paradox (39) . However, it may not be a major concern in the present study, because no strong association between enterolactone concentrations and colorectal cancer risk has been found in prospective studies (14) .…”
Section: Discussionmentioning
confidence: 57%
“…In a previous study based on the present cohort, we have found prior antibiotics use to mostly affect enterolactone levels in women (16) and higher enterolactone levels to be associated with lower risk of colorectal cancer among women, but with a higher risk among men (15) . Overall in other cohort studies, no association between enterolactone and risk of colorectal cancer has been found (14,40) . To the best of our knowledge, enterolactone and survival after colorectal cancer has not previously been studied.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…A szójában is megtalálható fitoösztrogének olyan növényi eredetű vegyületek, amelyek szerkezeti felépítése hasonlít az endogén ösztrogénhez, képesek az ER-okhoz kötődni, különösen az ERβ-hoz, és ezáltal az ERβ által mediált kedvező biológiai választ válthatnak ki. A fitoösztrogének az ER-hoz kötődve transzkripciós szinten szabályozhatják a sejtosztódást, az apoptózist, az angiogenezist vagy a sejtkapcsolatokat szabályozó gének kifejeződését, ami megmagyarázhatja, hogy a fitoösztrogének miért lehetnek hatékonyak a CRC bizonyos molekuláris altípusaiban és -az adenoma-carcinoma szekvencia meghatározott stádiumában alkalmazva -a CRC prevenciójában vagy kezelésében [42]. Klinikai vizsgálatokban igazolták, hogy a fitoösztrogéneket és növényi rostokat tartalmazó Eviendep (CM&D Pharma Limited, Egyesült Királyság) szedése már rövid távon is hatékonyan csökkenti a FAPos, illetve Lynch-szindrómás betegeknél az emésztőrendszeri polipok számát és méretét [43,44], és ezzel…”
Section: Neutrálisunclassified